The acute effect of different massage durations on squat jump, countermovement jump and flexibility performance in muay thai athletes - Ramazan Bayer; Özgür Eken (Physical Education of Students)
Background and Study Aim. Muay thai is a combat sport in which the competitors kick, punch, knee, elbow and growl with their opponents. The strength of the leg muscles can increase the intensity of the kick and its flexibility is a well-known issue for this sport. Determining the most appropriate method for these issues provides important gains to the athletes. One of the methods applied to achieve these gains is acute massage applications. The aim of the study is to evaluate the acute effect of different massage times on squat jump, countermovement jump and flexibility performance.